Luqman's advice to his son - Khan, S; Sarkar, Ramendranath (Goodword Books New Delhi, 2003)
Luqman's Advice to His Son from the Goodword series shares the timeless wisdom of Luqman as he imparts important life lessons to his son, emphasizing faith in God, good conduct, and humility. Through engaging storytelling, the book teaches children valuable moral guidance based on Quranic teachings.